The Third Mission of Universities: The Entrepreneurial University - Vefago, Yuri Borba; Trierweiller, Andréa Cristina; Barcellos de Paula, Luciano (Brazilian Journal of Operations & Production Management, 2020)
This article aims to analyze the productions in scientific journals of international bases, in English, Portuguese or Spanish, about entrepreneurial university and third mission, focusing on the productions of Brazilian authors, through a systematic search of the literature. For that, we use the SSF - Systematic Search Flow method, which is applied in systematic and integrative reviews. An enterprising university, committed to the development of its region, is the key factor in achieving regional innovation, a key institution in knowledge-based societies. In the age of knowledge, the university is as important as industry and government; fundamental for the development of knowledge and innovation. As a result, we identified research challenges and opportunities, contributing to the construction of a panorama of Brazilian scientific production in international journals on the themes entrepreneurial university and third mission.